2013
DOI: 10.1080/08946566.2013.751811
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural Variations in the Characteristics Associated With Elder Mistreatment in a Community-Dwelling Chinese Population

Abstract: This study compared the urban and rural differences in the sociodemographic, socioeconomic, health-related, and psychosocial factors associated with elder mistreatment (EM) in a Chinese population. Cross-sectional study of 269 urban and 135 rural participants aged 60 years or greater was performed. For urban participants, those with EM were more likely to be younger, have lower levels of education and income, and have lower levels of psychosocial well-being. For rural participants, those with EM were more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
2
26
1
4
Order By: Relevance
“…Considerando os critérios de inclusão, foram analisados 13 artigos, verificando-se diferenças nas definições conceituais e na metodologia, descritas com maior detalhe adiante. [33][34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Métodosunclassified
See 3 more Smart Citations
“…Considerando os critérios de inclusão, foram analisados 13 artigos, verificando-se diferenças nas definições conceituais e na metodologia, descritas com maior detalhe adiante. [33][34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Métodosunclassified
“…Os estudos têm sido direcionados, na sua maioria, para indivíduos com 60 ou mais anos de idade. 33,34,[36][37][38][39]41,43,45 Outros integram grupos etários de indivíduos com 65 ou mais anos de idade. 35,40,44 Em relação à definição de violência, na quase totalidade dos estudos é utilizada uma definição semelhante ou igual à proposta pela WHO 3 , à exceção de dois estudos em que apenas são apresentados os tipos de violência, mas sem ser definido este conceito.…”
Section: Desfechounclassified
See 2 more Smart Citations
“…Results from research on the relationship between elder abuse and physiological outcomes have been conflicting . While some studies found chronic illness and poor health to be contributing factors, a different study found no association between elder abuse and medical conditions . Meanwhile, a recent study found metabolic disorders to be more prevalent among older persons subjected to abuse.…”
Section: Introductionmentioning
confidence: 99%